The Algorithmic Dilemma: How AI is Redefining Informed Consent in Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Keywords: AI informed consent, digital health ethics, medical AI transparency, black-box systems, patient autonomy, data governance
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care